A new generalized paucituberculatan marsupial from the oligocene of Bolivia and the origin of 'shrew-like' opossums - Goin, Francisco Javier (2007)
Insights into the origin of 'shrew-like' oposssums of South America are gained thanks to a new fossil from the Oligocene Salla Beds in Bolivia. The specimen described here consists of a partial rostrum, palate and postcanine teeth, and shows several generalized features (cranial and dental) in the context of the Paucituberculata. On this basis we recognize Evolestes hadrommatos gen. et sp. nov. In order to evaluate the affinities of the new taxon, we performed a phylogenetic analysis including representatives of the Caenolestidae, Pichipilus and allies (not regarded here as caenolestids), Palaeothentidae, and Abderitidae, with three outgroups. Evolestes is the basalmost 'caenolestoid', and provides clues to the morphological changes involved in the origin of caenolestids.